+0  
 
0
272
1
avatar+644 

An infinite geometric series has first term -3/2 and sums to twice the common ratio. Find the sum of all possible values for the common ratio.

waffles  Sep 20, 2017

Best Answer 

 #1
avatar+20022 
+1

An infinite geometric series has first term -3/2 and sums to twice the common ratio.

Find the sum of all possible values for the common ratio.

 

If the common ratio r lies between −1 to 1 , we can have the sum of an infinite geometric series.

That is, the sum exits for \(| r |<1\) .

The sum S of an infinite geometric series with \( -1 is given by the formula, \(S=\frac{a_1}{1-r}\)

 

Let \(a_1 = -\frac{3}{2}\)

Let \( r =\,?\)

 

\(\begin{array}{|rcll|} \hline S = \frac{a_1}{1-r} &=& 2r \quad & | \quad a_1 = -\frac{3}{2} \\ \frac{-\frac{3}{2}}{1-r} &=& 2r \\ -\frac{3}{2} \cdot \frac{1}{1-r} &=& 2r \quad & | \quad : 2 \\ -\frac{3}{4} \cdot \frac{1}{1-r} &=& r \\ \frac{3}{4} \cdot \frac{1}{r-1} &=& r \quad & | \quad \cdot (r-1) \\ \frac{3}{4} &=& r \cdot (r-1) \quad & | \quad - \frac{3}{4} \\ r \cdot (r-1) - \frac{3}{4} &=& 0 \\ r^2-r- \frac{3}{4} &=& 0 \\\\ r &=& \frac{1\pm\sqrt{1-4\cdot (- \frac{3}{4}) } }{2} \\ r &=& \frac{1\pm\sqrt{1+3 } }{2} \\ r &=& \frac{1\pm 2 }{2} \\\\ r_1 &=& \frac{1 + 2 }{2} \\ r_1 &=& \frac{3}{2} \quad & | \quad \text{ no common ratio, because } r > 1 \\\\ r_2 &=& \frac{1 - 2 }{2} \\ r_2 &=& -\frac{1}{2} \\ \hline \end{array}\)

 

the sum of all possible values for the common ratio is \(-\frac12\)

 

laugh

heureka  Sep 20, 2017
 #1
avatar+20022 
+1
Best Answer

An infinite geometric series has first term -3/2 and sums to twice the common ratio.

Find the sum of all possible values for the common ratio.

 

If the common ratio r lies between −1 to 1 , we can have the sum of an infinite geometric series.

That is, the sum exits for \(| r |<1\) .

The sum S of an infinite geometric series with \( -1 is given by the formula, \(S=\frac{a_1}{1-r}\)

 

Let \(a_1 = -\frac{3}{2}\)

Let \( r =\,?\)

 

\(\begin{array}{|rcll|} \hline S = \frac{a_1}{1-r} &=& 2r \quad & | \quad a_1 = -\frac{3}{2} \\ \frac{-\frac{3}{2}}{1-r} &=& 2r \\ -\frac{3}{2} \cdot \frac{1}{1-r} &=& 2r \quad & | \quad : 2 \\ -\frac{3}{4} \cdot \frac{1}{1-r} &=& r \\ \frac{3}{4} \cdot \frac{1}{r-1} &=& r \quad & | \quad \cdot (r-1) \\ \frac{3}{4} &=& r \cdot (r-1) \quad & | \quad - \frac{3}{4} \\ r \cdot (r-1) - \frac{3}{4} &=& 0 \\ r^2-r- \frac{3}{4} &=& 0 \\\\ r &=& \frac{1\pm\sqrt{1-4\cdot (- \frac{3}{4}) } }{2} \\ r &=& \frac{1\pm\sqrt{1+3 } }{2} \\ r &=& \frac{1\pm 2 }{2} \\\\ r_1 &=& \frac{1 + 2 }{2} \\ r_1 &=& \frac{3}{2} \quad & | \quad \text{ no common ratio, because } r > 1 \\\\ r_2 &=& \frac{1 - 2 }{2} \\ r_2 &=& -\frac{1}{2} \\ \hline \end{array}\)

 

the sum of all possible values for the common ratio is \(-\frac12\)

 

laugh

heureka  Sep 20, 2017

29 Online Users

avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.